Assessing the impacts of agro - climatic conditions on annual trees in Ninh Thuan and Binh Thuan province - Vinh, Pham Quang; Binh, Nguyen Thanh; Huong, Bui Thi Thanh (Vietnam Journal of Earth Sciences, 2014)
In this article, the authors used Budget model to process the daily meteorological data of two meteorological stations Phan Thiet and Phan Rang (and refer 4 meteorological stations near the case study) in 30 years to calculate water balance in soil to assess the drought current for some annual trees in Ninh Thuan and Binh Thuan province, the driest region of Vietnam, to give the results of decreasing percentage productivity (%). By that way, the authors estimated the trend reducing agricultural crop yields due to drought. In the fact, insufficient amount of water would indicate the risks of desertification as well as filtering salt phenomenon in the region, the main direct reasons impact on agricultural productivity. The calculations were performed for two contrasting, sensitizing with drought and quite popular soil types in this area is that clay soil and arenosol. The results will be the believable scientific fundamentals for manager and farmer having solutions mitigating vulnerability by drought for agricultural tree, through planning crop calendar, agricultural trees adapting to drought, desertification and climate change.